1999
DOI: 10.3201/eid0504.990423
|View full text |Cite
|
Sign up to set email alerts
|

A Focus of Deer Tick Virus Transmission in the Northcentral United States

Abstract: We screened salivary glands from adult deer ticks collected near Spooner and Hayward, Wisconsin, to determine whether deer tick virus, a recently described flavivirus, occurs with other tickborne agents in the upper Midwest. Intraacinar inclusions suggestive of replicating virus were detected in 4 (4.6%) of 87 ticks. The virus was isolated by suckling-mouse inoculation. failed to right themselves when placed on their backs. By mid-afternoon they were moribund and died shortly thereafter. The time between ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 15 publications
6
68
0
Order By: Relevance
“…Although complete genome sequences may have provided additional information, short sequence fragments have often been used in population studies of arboviruses (10)(11)(12)(13). Additional criteria (maximum parsimony and maximum likelihood) may have provided corroboration for the close relationships observed; however, the sequences are so similar and the nodes on the neighbor-joining tree so poorly supported that additional analyses seemed unwarranted.…”
Section: Resultsmentioning
confidence: 99%
“…Although complete genome sequences may have provided additional information, short sequence fragments have often been used in population studies of arboviruses (10)(11)(12)(13). Additional criteria (maximum parsimony and maximum likelihood) may have provided corroboration for the close relationships observed; however, the sequences are so similar and the nodes on the neighbor-joining tree so poorly supported that additional analyses seemed unwarranted.…”
Section: Resultsmentioning
confidence: 99%
“…25 The DTV lineage was first detected by dissecting salivary glands from field-collected ticks removed from carcasses of dead deer or that were fed for 4 to 5 days on a naive New Zealand rabbit in the laboratory, staining one salivary gland of each tick with Feulgen reaction, and examining the salivary glands for evidence of virus growth. 12,26 The remaining salivary gland of each Feulgen-positive tick was pooled with those of four other ticks, placed in Hanks Balanced Salt Solution with 15% fetal bovine serum, homogenized, and intracerebrally inoculated into outbred CD-1 suckling mice. Injected mice subsequently were examined for illness.…”
Section: Discussionmentioning
confidence: 99%
“…1 A subtype of POWV, frequently termed deer tick virus (DTV), was first identified in 1995 2 and has subsequently been recognized as a human pathogen. 3 Because it is associated with the aggressively human-biting blacklegged or deer ticks (Ixodes scapularis), 4,5 this virus has been considered to pose a more significant threat to public health than the prototype virus, POWV, that is associated mainly with the relatively host-specific ticks Ixodes cookei and I. marxi. 6,7 Recent studies have suggested that the incidence of human POWV infection is increasing in the United States, 8 raising the possibility that POWV, like other members of the deer tick-associated guild of emerging zoonoses (Lyme disease, human babesiosis, and human granulocytic anaplasmosis), constitutes a mounting threat in regions where it is enzootic and where I. scapularis ticks are abundant.…”
Section: Introductionmentioning
confidence: 99%